Tackling the Challenge of Climate Change: A Near-Term Actionable Mitigation Agenda - Watson, R.; Nakicenovic; Rosenthal, E.; Goldenberg J; Srivastava L; Jiang K; Messner K; Anderson, K.; Ürge-Vorsatz D; Verchot, Louis V.; Grobmyer M; Calverley D; et al. (2014)
United Nations Secretary General Ban Ki-moon has invited world leaders to come to the Climate Summit on September 23, 2014 to deliver “bold pledges” to tackle climate change. This paper was prepared at the request of the Republic of Nauru, Chair of the Alliance of Small Island States, as part of their answer to that call.1 We believe the path to the global low-carbon transformation needed to tackle the climate crisis is within reach, but requires decisive political action from leaders around the world, now. This paper is unabashedly prescriptive on the need for action, but recognizes that there are multiple approaches and models from around the world that can be scaled up and adapted to national circumstances. Cost-effective technologies for a low-carbon economy are being implemented throughout the world, but at nowhere the scale and speed necessary. Emissions continue to rise. With every year of delay, human suffering, biodiversity loss, and the costs of mitigation and adaptation increase. We are running out of time.